The ethics of intergenerational risk - Paolo G. Piacquadio (University of Oslo, Department of Economics, 2015)
The paper reexamines the ethics of intergenerational risk. When risk re-solves gradually, earlier decisions cannot depend on the realization of later shocks and, consequently, some inequalities across generations are inevitable. To account for these inequalities, risky intergenerational situations are assessed in relation to an endogenous reference. The reference is specific to each intergenerational resource distribution problem and captures informa-tion about the technology, the intensity of risk, and the way risk resolves over time. The characterized class of reference-dependent utilitarian criteria avoids serious drawbacks of existing alternatives, such as discounted expected utilitarianism. Specifically, the welfare criteria: (i) disentangle aversion to intergenerational inequality from aversion to risk; (ii) value an early resolution of risk; and (iii) discount the future based on the intensity and the time-resolution of risk.
Keywords: D63; D81; H43; Q54; Q56; 330; Intergenerational justice; risk; social ordering; discounting